Teachers' Strategies in Introducing Literacy to Early Childhood: Lesson from Indonesia - Febiyanti, Anita; Kurniati, Euis; Emilly Nzunda, Ibrahim (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2021)
Purpose – This study aims to analyze teachers' strategies in introducing literacy to early childhood.Design/methods/approach –The researchers used the case study method. The research subjects are two teachers who teach in early childhood education institutions in Bandung, Indonesia.Findings –The results of this study indicate that in introducing literacy to children, teachers use multiple strategies, such as optimizing role-play activities, stimulation through active teacher conversations that encourage children to communicate (rich teacher talk), utilizing the use of big book media, and focusing on phonological awareness. The study results show that the teacher's role is significant in optimizing literacy learning for children.Research implications/limitations – This case study focuses on literacy learning in early childhood based on the experiences of two teachers in Bandung, Indonesia.Practical implications –This case study shows that multiple strategies are appropriate to introduce early childhood literacy and prepare children for the next level of education.Originality/value – This study contributes to the understanding of literacy in early childhood. In addition, this study recommends that teachers apply multiple strategies in introducing literacy through play activities. Paper type Case study